Bees of Santa Catarina Island, Brazila first survey and checklist (Insecta: Apoidea) - Steiner, Josefina; Harter-Marques, Birgit; Zillikens, Anne; Feja, Eduardo P. (Zootaxa, 2006)
On Santa Catarina Island bees were collected between 1999 and 2006 using various methods, including netting, trap nesting, and baiting. Vegetation types sampled comprised secondary forests, dunes, pastures, and parks. A checklist of 166 species of bees is presented. The family Apidae was represented by the highest number of species, followed by Megachilidae and Halictidae. Only a few species of Colletidae and Andrenidae were recorded. Species richness and occurrence of genera are compared to the results of other collections performed in the neighboring states of Paraná and Rio Grande do Sul.